Performance of cell free DNA as a screening tool based on the results of first trimester screening - Mahtab Motevasselian; Mohammad Amin Omrani; Soraya Saleh Gargari; Sarang Younesi; Mohammad Mahdi Taheri Amin; Pourandokht Saadati; Soudabeh Jamali; Mohammad-Hossein Modarresi; Shahram Savad; Majid Rahmani; Saloomeh Amidi; Saeed Delshad; et al. (Molecular Cytogenetics)
Abstract The advent of non-invasive prenatal testing (NIPT) in the screening of fetal abnormalities has optimized prenatal care and decreased the rate of invasive diagnostic tests. In this retrospective descriptive study, we began with 1874 singleton pregnancies. After exclusion of some cases, the study cohort ended up with 1674 cases. We analyzed the performance of NIPT based on the results of first trimester screening (FTS) using serum screening combined with NT. The cases were also compared to diagnostic testing/pregnancy outcomes. Notably, in the subgroup with FTS risk < 1000, NIPT was reported to be normal in all cases with no false negative results. In the risk group of 1/300-1/1000, NIPT could detect all trisomy 21 cases with one false positive result. Moreover, in the risk group of 1/11 − 1/300, NIPT could detect all cases of trisomy 21, 13 and 18 with low false positive rate. However, the false positive rate for sex chromosomal abnormalities was high. Taken together, the current study confirms the applicability of NIPT as a tool for detection of fetal trisomies with high sensitivity and specificity. Yet, the high rate of false positive results for sex chromosome abnormalities should be considered in the interpretation of the results.